2016
DOI: 10.7181/acfs.2016.17.3.140
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Analysis of the Nasal Septal Cartilage by Measurement Using Computed Tomography

Abstract: BackgroundThe nasal septal cartilage is often used as a donor graft in rhinoplasty operations but can vary widely in size across the patient population. As such, preoperative estimation of the cartilaginous area is important for patient counseling as well as operating planning. We aim to estimate septal cartilage area by using facial computed tomography (CT) studies.MethodsThe study was performed using facial CT images taken from 200 patients between January 2012 to July 2015. Using the mid-sagittal image, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
2
3
0
2
Order By: Relevance
“…1,11,13 This overlap decreased with age, which is probably because of the gradual ossification of the septal cartilage along the junction between the septal cartilage and the perpendicular plate of the ethmoid bone. [16][17][18] This measurement did not differ between subgroups with and without a nasal hump, which Palhazi et al have also reported. 1 Lazovic et al described two different types of nasal bones: S-shaped nasal bones and V-shaped nasal bones.…”
Section: Discussionsupporting
confidence: 67%
“…1,11,13 This overlap decreased with age, which is probably because of the gradual ossification of the septal cartilage along the junction between the septal cartilage and the perpendicular plate of the ethmoid bone. [16][17][18] This measurement did not differ between subgroups with and without a nasal hump, which Palhazi et al have also reported. 1 Lazovic et al described two different types of nasal bones: S-shaped nasal bones and V-shaped nasal bones.…”
Section: Discussionsupporting
confidence: 67%
“…Nevertheless, it is still challenging for surgeons to ensure complete filling of these large perforations. 24,25 In our study, the size of the biopsy was comparable to small-to-medium septum perforations in humans.…”
Section: Discussionsupporting
confidence: 63%
“…В ходе работы подтвердилось, что конуснолуче вая КТ -чрезвычайно информативная, неинвазив ная и объективная методика исследования [9], позво ляющая выявлять анатомические особенности поло сти носа до операционного вмешательства гораздо точнее субъективной оценки хирурга.…”
Section: результаты и обсуждениеunclassified
“…определили по данным компьютерной томографии (КТ) разме ры перегородочного хряща и рекомендуемый объем забора при сохранении адекватной Lраспорки у ко рейцев. В частности, площадь хряща варьировала в пределах 4,89-12,42 см 2 [9]. Этнические особенно сти морфологии, размера ПН и ее связи с другими аспектами лицевого скелета у европейцев и афри канцев с помощью КТ исследовали N. Holton и со авт.…”
unclassified